2002
DOI: 10.1029/2002gl015708
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clouds on erythemal and total irradiance as derived from data of the Argentine Network

Abstract: [1] Ultraviolet (UV) erythemal and total (300 -3000 nm) irradiance measurements of the Argentine Servicio Meteorológico Nacional Network were related to groundbased cloud observations. No geographical dependence was observed in the effects of each cloud-type on the irradiance, from tropical to Antarctic regions. For overcast conditions, median transmittance percentages with respect to the clearsky situation of 81%, 44% and 36% at high, medium and low clouds respectively for erythemal irradiance, and 83%, 30% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 13 publications
3
35
0
1
Order By: Relevance
“…Those circulation anomalies then drive variability in cloud cover and thus variability in UV radiation reaching the boundary layer, which in turn is seen in phase-to-phase variability in surface ozone concentrations in Mexico City. The cloud-UV radiation portion of our hypothesis is supported by Kerr and Fioletov (2008), who found that typical UV transmission ratios range between 0.3 and 0.8 for overcast conditions (Cede et al, 2002) and as little as 0.05 for thick cumulonimbus clouds (McArthur et al, 1999). It is also supported by An et al (2008), who found a strong relationship between surface ozone concentrations in Beijing and surface UV radiation, particularly in summer, and noted that surface UV was up to 200 % more sensitive to total cloud cover than was surface total radiation.…”
Section: Introductionsupporting
confidence: 72%
“…Those circulation anomalies then drive variability in cloud cover and thus variability in UV radiation reaching the boundary layer, which in turn is seen in phase-to-phase variability in surface ozone concentrations in Mexico City. The cloud-UV radiation portion of our hypothesis is supported by Kerr and Fioletov (2008), who found that typical UV transmission ratios range between 0.3 and 0.8 for overcast conditions (Cede et al, 2002) and as little as 0.05 for thick cumulonimbus clouds (McArthur et al, 1999). It is also supported by An et al (2008), who found a strong relationship between surface ozone concentrations in Beijing and surface UV radiation, particularly in summer, and noted that surface UV was up to 200 % more sensitive to total cloud cover than was surface total radiation.…”
Section: Introductionsupporting
confidence: 72%
“…Thus, the total global solar radiation is usually more attenuated by clouds than erythemal UV. This is caused by the much higher contribution from the direct component for total global radiation than for erythemal radiation [48]. One additional reason for the different effects of clouds on erythemal and total global solar radiation is the fact that water does not absorb in the UV, but it has strong absorption bands mainly in the infrared band [48].…”
Section: Cloudsmentioning
confidence: 98%
“…Enhancements up to 25% in the UV region have been reported by many investigators [43,49]. Enhancement episodes can last for hours [48]. Pfister et al [50] analysed one year of total global irradiance measurements at Lauder, New Zealand, and found that measured radiation enhancements of more than 10% appeared with a frequency of 5%.…”
Section: Cloudsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these enhancements can reach values of up to 30% over clear-sky values during several minutes in a row, pointing out the importance of these events [4,5] . The enhancements were found to be most pronounced for large cloud cover of 5 to 7 oktas when the solar disk is unclouded [6], being smaller in the UV band than in the visible and infrared intervals [7]. It is well documented that these short-term enhancements in UV levels may affect the photosynthesis rate of vegetation like marine algae or phytoplankton [8].…”
Section: Introductionmentioning
confidence: 96%